Analyses of the behavioural preferences of generation X to drive up the adoption of digital payments among them - Shakul Srivastava (International Journal of Advanced Science and Technology, 2020)
Studies have suggested and there is evidence that it is important to understand the customer really well before you can make them buy your proposed offering. When it comes to digital payment methods, people of generation X have been found to be very circumspect. They have not taken so well to these as the millennial people. The purpose of this paper is to identify what matters to the people of Generation X the most when it comes to digital modes of payment. For this convenience sampling technique was used and a questionnaire was shared with a set of people in the target demographic to get their opinion. The questions were both qualitative and quantitative in nature. The study first identified the preferred payment mode for the target demographic. It was found that people of generation X still preferred cash. Then, there was an attempt to find out their payment habits across channels. It was revealed that the preferred mode of payment changes with the channel. It was found out that while cash is preferred for offline payments, cards and net banking are preferred when shopping online. In the final stage, we tried to find out what was important to generation X when it came to digital payment products. These findings were quantified and analysed. To test for consistency in responses, Chronbach Alpha test was used. Thereafter, a multiple regression test was run to identify the significant variables and their influence. Security came across as the most important thing in the way of adoption of digital payments solutions